Storage vs repair bandwidth for network erasure coding in distributed storage systems - Singal, Swati Mittal; Rakesh, Nitin; Matam, Rakesh (2015 International Conference on Soft Computing Techniques and Implementations (ICSCTI), 2015)
Network coding is used in peer-to-peer storage systems, archival storage, wireless networks, satellite communication, video conferencing etc. Storage system stores data at different locations. For the data to be available, durable and reliable, it must be able to recover from failures efficiently. Different approaches applied for recovery in storage systems are examined and evaluated in this paper. Keeping replicas of the data at multiple places is traditional technique used by major storage systems. To reduce the amount of storage required by replication the distributed system is now transitioning towards, the erasure codes. Several approaches like the hybrid and regenerating codes provide solution to storage and repair bandwidth. But still improvement in terms of communication cost in the face of failures is required. The approaches and main application areas of these approaches are examined and analyzed in this paper. A comparative analysis based on storage requirement, disk access, repair bandwidth and unavailability probability is also presented.